Más allá del castigo: el surgimiento del movimiento de víctimas en los Estados Unidos y Suecia = Beyond punishment : the emergence of victim movements in the U.S. and Sweden - Gallo, Carina (Revista de victimología, 2018)
Classical victimology has accepted the idea that victims and offenders are different and opposed. In this line of argument, it seems that victims can obtain satisfaction through the lowering of the guarantees for suspects and detainees, and the increase of punishment. This perspective has been promoted by the United States, followed by other countries like the United Kingdom. However there is at least one model that differs from them: the Swedish case. Facing the lack of research on the global increase of services for victims, this article intends to clarify this by a comparative analysis between the United States and Sweden. In the States, the promotion of services for victims is connected to a harsh punitive criminal policy. By contrast, in Sweden, improving the rights of victims is related to the idea of human rights, treatment and support. This study shows different possible approaches to victims and crime, in diverse cultural contexts, as well as realistic possibilities of applying these policies in other countries. Finally, this text questions the dominant assumptions about how to help victims in a better way